Hubungan Ketimpangan Pendapatan dan Pertumbuhan Ekonomi di Sumatera Barat : Pembuktian Hipotesis Kuznet - Oktarina, Nabila; Yuliana, Yeni (Jurnal Greenation Ilmu Akuntansi, 2023)
Abstract: This study aims to analyze and find out: (1) the relationship between per capita income and income inequality in West Sumatra. (2) the level of income inequality between regions in West Sumatra based on the Gini ratio index analysis. (3) proving the Kuznets curve hypothesis in West Sumatra. This type of research is descriptive and associative research. This research uses an analytical tool with the Ordinary Least Squared (OLS) method. The results of the study concluded that (1) per capita income has a significant effect on development inequality in West Sumatra. (2) the level of development inequality between districts/cities in West Sumatra is not too high. This can be seen from the average level of development inequality in West Sumatra, which is seen from the gini ratio of 0.313. (3) the Kuznets curve hypothesis in West Sumatra is proven to be accepted. Abstrak: Penelitian ini bertujuan untuk menganalisis dan mengetahui : (1) hubungan pendapatan per kapita terhadap ketimpangan pendapatan di Sumatera Barat. (2) tingkat ketimpangan pendapatan antar wilayah di Sumatera Barat berdasarkan analisis indeks Gini rasio. (3) pembuktian hipotesis kurva Kuznet di Sumatera Barat. Jenis penelitian ini adalah penelitian deskriptif dan asosiatif.. Penelitian ini menggunakan alat analisis dengan metode Ordinary Least Squared (OLS). Hasil penelitian menyimpulkan bahwa (1) Pendapatan per kapita berpengaruh signifikan terhadap ketimpangan pembangunan di Sumatera barat. (2) tingkat ketimpangan pembangunan antar kabupaten/kota di Sumatera Barat tidak terlalu tinggi hal ini terlihat dari rata-rata tingkat ketimpangan pembangunan di Sumatera Barat yang dilihat dari gini rasio sebesar 0,313. (3) hipotesis kurva Kuznet di Sumatera Barat terbukti diterima.